Mercury thiogallate nanosecond optical parametric oscillator continuously tunable from 4.2 to 10.8 μm. (22nd July 2015) - Kostyukova, N Yu; Kolker, D B; Zenov, K G; Boyko, A A; Starikova, M K; Sherstov, I V; Karapuzikov, A A
Abstract: We demonstrate an optical parametric oscillator based on two HgGa2 S4 crystals with an extremely wide tuning range from 4.2 to 10.8 μ m. The HgGa2 S4 optical parametric oscillator was pumped by a Q-switched nanosecond Nd : YLF laser at 1.053 μ m. The absorption spectrum of ammonia was presented to demonstrate the feasibility of the developed optical parametric oscillator system for spectroscopic measurements and gas detection.